A multicentre study on spontaneous in-cage activity and micro-environmental conditions of IVC housed C57BL/6J mice during consecutive cycles of bi-weekly cage-change - B. Ulfhake; H. Lerat; J. Honetschlager; K. Pernold; M. Rynekrová; K. Escot; C. Recordati; R. V. Kuiper; G. Rosati; M. Rigamonti; S. Zordan; J.-B. Prins (PLoS ONE, 2022)
Mice respond to a cage change (CC) with altered activity, disrupted sleep and increased anxiety. A bi-weekly cage change is, therefore, preferred over a shorter CC interval and is currently the prevailing routine for Individually ventilated cages (IVCs). However, the build-up of ammonia (NH3) during this period is a potential threat to the animal health and the literature holds conflicting reports leaving this issue unresolved. We have therefor examined longitudinally in-cage activity, animal health and the build-up of ammonia across the cage floor with female and male C57BL/6 mice housed four per IVC changed every other week. We used a multicentre design with a standardised husbandry enabling us to tease-out features that replicated across sites from those that were site-specific. CC induce a marked increase in activity, especially during daytime (~50%) when the animals rest. A reduction in density from four to two mice did not alter this response. This burst was followed by a gradual decrease till the next cage change. Female but not male mice preferred to have the latrine in the front of the cage. Male mice allocate more of the activity to the latrine free part of the cage floor already the day after a CC. A behaviour that progressed through the CC cycle but was not impacted by the type of bedding used. Reducing housing density to two mice abolished this behaviour. Female mice used the entire cage floor the first week while during the second week activity in the latrine area decreased. Measurement of NH3 ppm across the cage floor revealed x3 higher values for the latrine area compared with the opposite area. NH3 ppm increases from 0–1 ppm to reach ≤25 ppm in the latrine free area and 50–100 ppm in the latrine area at the end of a cycle. As expected in-cage bacterial load covaried with in-cage NH3 ppm. Histopathological analysis revealed no changes to the upper airways covarying with recorded NH3 ppm or bacterial load. We conclude that housing of four (or equivalent biomass) C57BL/6J mice for 10 weeks under the described conditions does not cause any overt discomfort to the animals.